INVERSI DAN TITIK-TITIK HARMONIS - himmawati puji; Caturiyati Caturiyati (Pythagoras: Jurnal Matematika dan Pendidikan Matematika, 2007)
Given a circle centre O and radius r in , the inversion in this circle is the mapping defined by , where lies on the straight line through O and A, and on the same side of O as A, and . It will be investigated the property of inversion related to four harmonic points. The result is that the cross-ratio of any four coplanar points A, B, C, D is invariant under inversion. Hence, the inversion preserves the four harmonic points.Keywords : inversion, cross ratio, four harmonic points.